1988
DOI: 10.1111/j.1476-5381.1988.tb11407.x
|View full text |Cite
|
Sign up to set email alerts
|

The cholecystokinin receptor antagonist L364,718 increases food intake in the rat by attenuation of the action of endogenous cholecystokinin

Abstract: To determine the role of endogenous cholecystokinin (CCK) in the regulation of food intake, the effects of the potent CCK receptor antagonist L364,718 were investigated on the intake of a palatable diet in non‐deprived rats. The effect of a single dose of proglumide was also investigated for comparative purposes. In addition, the ability of L364,718 to antagonize the reduction in food intake produced by exogenous cholecystokinin‐octapeptide (CCK8) or bombesin in food‐deprived rats was determined. L364,718 (10–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
49
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(57 citation statements)
references
References 19 publications
8
49
0
Order By: Relevance
“…These include cholecystokinin (CCK), glucagon-like peptide 1 (GLP1), apolipoprotein A-IV, enterostatin, gastrin-releasing peptide (a member of the bombesin family), oxyntomodulin, amylin and peptide YY. CCK administration causes reduced food intake, 55 while antagonists to CCK A receptors substantially increase food intake; 56 thus, endogenous CCK has a role in controlling meal size. The satiety-inducing effects of CCK require an intact vagus nerve.…”
Section: Vagal Mucosal Afferentsmentioning
confidence: 99%
“…These include cholecystokinin (CCK), glucagon-like peptide 1 (GLP1), apolipoprotein A-IV, enterostatin, gastrin-releasing peptide (a member of the bombesin family), oxyntomodulin, amylin and peptide YY. CCK administration causes reduced food intake, 55 while antagonists to CCK A receptors substantially increase food intake; 56 thus, endogenous CCK has a role in controlling meal size. The satiety-inducing effects of CCK require an intact vagus nerve.…”
Section: Vagal Mucosal Afferentsmentioning
confidence: 99%
“…Furthermore, experiments with L-364,718 provided support for the physiologic significance of endogenous CCK-8 as a mediator of feeding behavior. Administration of L-364,718 alone to mice, rats, pigs, or monkeys increases food intake when assessed using a variety of feeding paradigms (7)(8)(9)(11)(12)(13). In addition, it was reported that L-364,718 enhanced hunger ratings in humans (14).…”
Section: Introductionmentioning
confidence: 99%
“…They were injected with 0, 10.0, 30.0 and 100.0 yg kg-1, respectively, of (Dourish et al, 1988b;Hewson et al, 1988;Reidelberger et al, 1988 (Neill & Cooper, 1989 (Cooper, 1986;Cooper et al, 1985a) to produce a suppression of palatable food intake similar to 3.0mg kg-' of ( + )-fenfluramine.…”
Section: Methodsmentioning
confidence: 99%
“…range of doses from 1 pg kg-1 to 10mg kg-1 (i.p. ), antago-nized the anorectic effect of CCK-octapeptide, but not of bombesin (Lotti et al, 1987;Dourish et al, 1988b;Hewson et al, 1988; Khosla & Crawley, 1988;Reidelberger et al, 1988).…”
Section: Introductionmentioning
confidence: 99%